From social networks to bird enthusiasts: reporting interactions between plastic waste and birds in Peru. (16th June 2023) - Ayala, Félix; Vizcarra, Jhonson K.; Castillo-Morales, Karen; Torres-Zevallos, Uriel; Cordero-Maldonado, Cristel; Ampuero-Merino, Lyanne; Herrera-Peralta, Kárlom; De-la-Torre, Gabriel Enrique; Angulo, Fernando; Cárdenas-Alayza, Susana
Summary: Peru has the second-highest diversity of birds in the world, but little is known about the interactions between birds and plastic waste. To fill this knowledge gap, we searched the scientific literature, collected information from social networks such as Facebook and databases such as Macaulay Library and iNaturalist and solicited records through messaging with researchers and bird enthusiasts. We found 119 bird interactions with plastic debris involving 39 species from 20 families, with the red-legged cormorant Phalacrocorax gaimardi and the neotropical cormorant Phalacrocorax brasilianus being the most affected species. By type of interaction category, plastic waste in nests was the most abundant, followed by entanglement, capture and handling and ingestion. Ropes, nets and soft plastics such as bags were the most frequently reported types of waste. As our methodology has limitations, it is probable that other species that also interact with plastic waste have not been reported, so we recommend further study.